Multimodal Features in Teacher’s Developed Teaching Materials: A Study at SMPN 1 Waru - Ayati, Afifah Nurul; Madjid, Hilda Izzati; Lukmansono, Toto (ICONELT, 2024)
This article aims to address the research concerning features of multimodality that are present in the teaching materials developed by English teachers at SMPN 1 Waru. The study uses a content analysis to examine teaching materials developed by English teachers. Using Kress and van Leeuwen’s multimodal theory, the finding of this research shows four multiple modes in the teachers’ developed teaching materials. Those four modes covering visual, verbal, audio, and spatial work together in facilitating the students’ understanding about the topic. The result of this study also highlights the importance of utilizing multiple modes in enhancing the students’ readability of the materials.